Musculoskeletal Changes Across the Lifespan: Nutrition and the Life-Course Approach to Prevention - Azzolino, Domenico; Spolidoro, Giulia Carla Immacolata; Saporiti, Edoardo; Luchetti, Costanza; Agostoni, Carlo; Cesari, Matteo (Frontiers in Medicine, 2021)
Aging is characterized by the progressive decline of muscle mass and function, the so-called sarcopenia. Also bone loss is widespread among older people. Sarcopenia and osteopenia/osteoporosis are associated with several adverse outcomes including falls, risk of fractures, functional decline, frailty, and mortality. Recently, the life-course approach to prevent or delay functional decline has become very popular. Regarding musculoskeletal health, there is suggestive evidence that acting during critical or sensitive periods of life in which each person build-up its biological reserves may influence the rate of functional decline in the later stages of life. A life-course approach to musculoskeletal health should take place during early life when plasticity allows more easily the attainment of the peak of the musculoskeletal system driven by environmental stimuli. The rate of the subsequent decline will depend on the peak previously reached. Nutrition and physical exercise are important environmental factors that can influence musculoskeletal development by favoring and maintaining peak bone and muscle mass and strength. Here we provide an overview of body composition changes occurring across the lifespan and strategies based on nutrition and physical exercise to support musculoskeletal health as well as minimizing losses during older life.